The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1186/1756-0500-7-116
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and sequencing of swine carbonic anhydrase VI, an enzyme expressed in the swine kidney

Abstract: BackgroundCarbonic anhydrase VI (CA-VI) is produced by the salivary gland and is secreted into the saliva. Although CA-VI is found in the epithelial cells of distal straight tubule of swine kidneys, the exact function of CA-VI in the kidneys remains unclear.ResultsCA-VI was located in the epithelial cells of distal straight tubule of swine kidneys.A full-length cDNA clone of CA-VI was generated from the swine parotid gland by reverse transcription polymerase chain reaction, using degenerate primers designed ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…51 It is also produced in the nasal gland 52 and the kidney. 53 It was reported that urinary CAH6 might represent a biomarker for kidney disease in pigs, particularly for disorders affecting distal straight tubules. 54 Its role following ESWT administration is not clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…51 It is also produced in the nasal gland 52 and the kidney. 53 It was reported that urinary CAH6 might represent a biomarker for kidney disease in pigs, particularly for disorders affecting distal straight tubules. 54 Its role following ESWT administration is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…This enzyme is abundantly found in salivary glands, and saliva has been implicated in taste and gastrointestinal dysfunctions, tooth erosion, and caries 51 . It is also produced in the nasal gland 52 and the kidney 53 . It was reported that urinary CAH6 might represent a biomarker for kidney disease in pigs, particularly for disorders affecting distal straight tubules 54 .…”
Section: Discussionmentioning
confidence: 99%